Epithelial Properties of the Second Heart Field. Issue 1 (5th January 2018) - Cortes, Claudio; Francou, Alexandre; De Bono, Christopher; Kelly, Robert G.
Abstract : The vertebrate heart tube forms from epithelial progenitor cells in the early embryo and subsequently elongates by progressive addition of second heart field (SHF) progenitor cells from adjacent splanchnic mesoderm. Failure to maximally elongate the heart results in a spectrum of morphological defects affecting the cardiac poles, including outflow tract alignment and atrioventricular septal defects, among the most common congenital birth anomalies. SHF cells constitute an atypical apicobasally polarized epithelium with dynamic basal filopodia, located in the dorsal wall of the pericardial cavity. Recent studies have highlighted the importance of epithelial architecture and cell adhesion in the SHF, particularly for signaling events that control the progenitor cell niche during heart tube elongation. The 22q11.2 deletion syndrome gene Tbx1 regulates progenitor cell status through modulating cell shape and filopodial activity and is required for SHF contributions to both cardiac poles. Noncanonical Wnt signaling and planar cell polarity pathway genes control epithelial polarity in the dorsal pericardial wall, as progenitor cells differentiate in a transition zone at the arterial pole. Defects in these pathways lead to outflow tract shortening. Moreover, new biomechanical models of heart tube elongation have been proposed based on analysis of tissue-wide forces driving epithelial morphogenesis in the SHF, including regional cell intercalation, cell cohesion, and epithelial tension. Regulation of the epithelial properties of SHF cells is thus emerging as a key step during heart tube elongation, adding a new facet to our understanding of the mechanisms underlying both heart morphogenesis and congenital heart defects.